Pregnancy in acute and chronic ulcerative colitis: Case reports (Indian Journal of Case Reports, 2020)
Ulcerative colitis is an autoimmune idiopathic chronic relapsing inflammatory bowel disease involving the mucosa and the submucosa of the large bowel starting at the rectum. Acute disease occurring for the first time in pregnancy is not common and has the Truelove and Witt’s criteria for defining acute ulcerative colitis. Acute ulcerative colitis in pregnancy is difficult to diagnose and carries the risk of pre-term birth as well as fetal growth restriction along with fetal malformations if not treated aggressively. Drugs and investigations safe in pregnancy along with appropriate care of the patient can improve the pregnancy outcome and patient’s health. Chronic ulcerative colitis patients have exacerbations in pregnancy or early postpartum. These patients may have poor absorption in spite of proper medication and have difficulty in building up the hemoglobin levels during pregnancy. Here, we are reporting two cases, one each of acute as well as chronic ulcerative colitis in pregnancy with their investigations, treatment, and outcome in respect to maternal health during the entire pregnancy as well as fetal growth and complications.